Effects of Plants' Ingredients on Dough and Final Product - Mironeasa, Silvia (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The Special Issue presents valuable information on the perspective of using cereals/pseudocereal grains, vegetable byproducts, or flour processed by applying various techniques in baked goods and pasta products. At the same time, this Special Issue reveals the experience of authors regarding the use of plants' ingredients as a valuable strategy to improve the nutritional profile of food products, contributing to the reduction in nutrient deficiencies, or to make products for special nutrition such as low-sodium or gluten-free ones. The quality of the raw materials, the processing techniques, and the potential of certain vegetable byproducts from fruits or oilseeds represent key aspects for obtaining qualitatively enhanced food products. Furthermore, current approaches to diversify the range of bakery and pasta products which offer health benefits to consumers are also presented in this Special Issue.